2015
DOI: 10.1007/s11357-015-9852-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Pilates exercise program on muscle strength, postural control and body composition: results from a pilot study in a group of post-menopausal women

Abstract: Participation in exercise programs is heartily recommended for older adults since the level of physical fitness directly influences functional independence. The aim of this present study was to investigate the effects of supervised Pilates exercise training on the physical function, hypothesizing that a period of Pilates exercise training (PET) can increase overall muscle strength, body composition, and balance, during single and dual-task conditions, in a group of post-menopausal women. Twenty-five subjects, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
50
0
9

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 36 publications
9
50
0
9
Order By: Relevance
“…The innovative findings of this study were the significant increases on PhA and handgrip strength and decreases on %F in older women after a suspension exercise training program, regardless of age and BMI. Several studies have pointed out that traditional forms of physical activity, such as resistance and aerobic training, contribute to increased PhA and reduce fat mass in older adults [4,9,17]. To the authors' knowledge, this is the first study that investigated the effects of this new kind of training in a geriatric population.…”
Section: Discussionmentioning
confidence: 87%
“…The innovative findings of this study were the significant increases on PhA and handgrip strength and decreases on %F in older women after a suspension exercise training program, regardless of age and BMI. Several studies have pointed out that traditional forms of physical activity, such as resistance and aerobic training, contribute to increased PhA and reduce fat mass in older adults [4,9,17]. To the authors' knowledge, this is the first study that investigated the effects of this new kind of training in a geriatric population.…”
Section: Discussionmentioning
confidence: 87%
“…A number of studies have shown that Pilates exercise programmes reduce both pain and disability (Choon Wyn Lim, Li Choo Poh, Ying Low, & Pong Wong, 2011;Natour, de Araujo Cazotti, Ribeiro, Baptista, & Jones, 2014;Quinn et al, 2011). Improvements in strength and function (Cancela, de Oliveira, de Oliveira, & de Almeida Pres-Oliveira, 2014;Donzeli Viera et al, 2017), better static and dynamic balance and improved walking parameters are associated with a reduced risk of falls (Bullo et al, 2015;Newell, Shead, & Sloan, 2012;Pata, Lord, & Lamb, 2014). Furthermore, some studies have reported improvements in quality of life and mood (Bullo et al, 2015;de Oliveira, de Oliveira, & de Almeida Pres-Oliveira, 2015;Ferreira et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Exercise training is one of the interventions reported to reduce the risk of all-cause and cardiovascular mortality by 30% and prevent loss of muscle mass and strength, increase the oxidative capacity of skeletal muscles, exert anti-inflammatory effects, and thereby, postpone agerelated muscle deteriorations (5). In the early 20th century, Joseph Pilates suggested a physical fitness system, called Pilates, that is well established to elicit numerous healthbeneficial effects and has the potential to counteract agerelated diseases, such as metabolic syndrome and diabetes (6,7).…”
Section: Introductionmentioning
confidence: 99%